Low-temperature-resistant anti-seepage carbon fiber reinforced composite material and preparation method thereof

By introducing polyamic acid-grafted hydroxylated nano-silica and nano-rubber onto the surface of carbon fibers, a multi-level reinforced interface layer is formed, which solves the leakage problem of carbon fiber composites in low-temperature media, achieving high compatibility and low leakage rate, and is suitable for aerospace propellant tanks and other fields.

CN121374903AActive Publication Date: 2026-01-23SUZHOU LABORATORY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511984852.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-01-23
Estimated Expiration
2045-12-26

AI Technical Summary

Technical Problem

The compatibility and leakage problems of carbon fiber composites with liquid oxygen in cryogenic media have not been effectively solved. Existing methods cannot effectively suppress the generation and propagation of microcracks, leading to increased leakage rates and potential safety hazards.

Method used

A multi-level interface structure with liquid oxygen compatibility and high toughness was adopted and combined with a highly impermeable thermoplastic resin to prepare carbon fiber reinforced fluororesin composite material. By introducing polyamic acid-grafted hydroxylated nano-silica and nano-rubber on the surface of carbon fibers, a multi-level reinforcing interface layer was formed, which improved the interfacial bonding ability and material density.

Benefits of technology

It achieves ultra-low leakage rate and high compatibility at ultra-low temperatures. After 50 thermal cycles from -196℃ to 120℃, the material has a permeability of less than 1×10-8 Pa·m3/s, an interlaminar shear strength retention rate of ≥90%, and good liquid oxygen compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of composite materials, and particularly relates to a low-temperature-resistant anti-seepage carbon fiber reinforced composite material and a preparation method thereof. The preparation method comprises the following steps: dispersing polyamide acid grafted hydroxylated nano silicon dioxide in a solvent, adding nano rubber, and carrying out ultrasonic treatment to obtain a sizing agent; dipping the desized carbon fibers in a sizing agent, taking out and drying to obtain sized carbon fibers; the polytrifluorochloroethylene resin and the sizing carbon fiber are compounded, and a carbon fiber reinforced polytrifluorochloroethylene prepreg tape is obtained; polyethersulfone resin and polyphenylene sulfide resin are blended and compounded with the sizing carbon fibers, and a carbon fiber reinforced polyethersulfone / polyphenylene sulfide resin prepreg tape is obtained; laying the carbon fiber reinforced polytrifluorochloroethylene prepreg tape on the inner layer, laying the carbon fiber reinforced polyethersulfone / polyphenylene sulfide resin prepreg tape on the outer layer, and curing and molding to obtain the carbon fiber reinforced polytrifluorochloroethylene / polyphenylene sulfide composite material. The carbon fiber composite material disclosed by the invention not only can keep high-super mechanical properties, but also has an ultralow leakage rate under ultralow-temperature circulation.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of carbon fiber reinforced composite materials, and particularly relates to a low-temperature-resistant anti-permeation carbon fiber reinforced composite material and a preparation method thereof. BACKGROUND

[0002] The development of space vehicle tank materials mainly experiences the stages of aluminum-magnesium alloy, aluminum-copper alloy, aluminum-lithium alloy, and finally develops towards carbon fiber composite materials. The specific strength and specific stiffness of carbon fiber composite materials are much higher than those of metals, and the carbon fiber composite materials have good fatigue resistance, vibration resistance, and good forming process, and are particularly suitable for application in large structures and integral structure forming, which can reduce the number of parts and connection processes, and are ideal materials for realizing high performance and light weight of aerospace advanced equipment structures. Compared with metal tanks, carbon fiber composite material tanks can reduce the weight of liquid oxygen tank structures by about 25%, and the larger the size of the low-temperature medium tank structure, the more obvious the weight reduction effect, and the overall launch cost is reduced. Therefore, the development of carbon fiber composite material tanks has become an inevitable trend.

[0003] Since the carbon fiber composite material exhibits certain oxidation resistance, but the key thermal properties such as ignition point, flash point and thermal decomposition temperature are lower than those of metal materials. When encountering high-energy instantaneous impact, the carbon fiber composite material may trigger a fire risk due to local rapid heating, and even may further cause an explosion accident. Therefore, improving the compatibility of carbon fiber composite materials with liquid oxygen is the primary core problem to be solved. In addition, due to the obvious difference between the thermal expansion coefficient of carbon fiber and the thermal expansion coefficient of the resin matrix, when the carbon fiber composite material cools from the forming temperature to room temperature, and is applied to low-temperature tanks such as liquid oxygen and liquid hydrogen, the thermal expansion mismatch will cause the deformation of carbon fiber and epoxy resin to be uncoordinated, resulting in high residual stress of the carbon fiber composite material at low temperature cooling, which is easy to produce microcracks at the resin matrix, carbon fiber and resin interface under the coupling action of internal mechanical stress. Under the continuous or cyclic action of low temperature and stress, the microcracks continuously expand until single-layer transverse cracks and interlayer cracks are formed, and then a leakage channel is formed to cause tank leakage; the leakage failure of the carbon fiber composite material low-temperature tank will occur before the structural load failure, which is extremely dangerous for flammable and explosive propellants such as liquid oxygen and liquid hydrogen. Therefore, how to effectively improve the liquid oxygen compatibility of carbon fiber composite materials, while effectively inhibiting the leakage problem of the carbon fiber composite materials in the ultra-low temperature medium, is the key to the application of carbon fiber composite materials in ultra-low temperature medium tanks.

[0004] In order to improve the low-temperature medium leakage resistance of carbon fiber composite materials, the prior art usually introduces flexible polymers (such as thermoplastic resins, nano rubber, etc.) or dopes nano materials (such as carbon nanotubes, silicon dioxide, etc.) in the resin matrix to improve the toughness of the resin matrix, so as to improve the crack propagation resistance and reduce the leakage risk. However, the above research and method cannot fundamentally solve the problem of microcrack caused by residual stress. The introduction of flexible polymers may make the thermal expansion coefficient of the resin matrix larger. When the environment temperature of the carbon fiber reinforced resin matrix composite material decreases from room temperature to ultra-low temperature, the temperature stress of the resin / fiber interface increases sharply due to the larger thermal expansion coefficient of the resin matrix, and then the microcrack of the resin / fiber interface is easily generated, which causes the leakage rate to increase. The nano materials are prone to agglomeration in the resin matrix, and if the surface lacks active functional groups, the interface bonding between the nano materials and the resin matrix will be weakened, resulting in the decrease of the mechanical properties of the carbon fiber composite material.

[0005] The thermal expansion coefficients of the commonly used epoxy resin matrix and carbon fiber are quite different, which will generate huge thermal stress, resulting in the generation and propagation of microcracks. These microcracks will become the penetration channels of the medium (especially ultra-low temperature liquid and gas), causing the leakage rate to increase, which is extremely dangerous for flammable and explosive propellants (such as liquid oxygen and liquid hydrogen). Fluororesin is known for its extremely low permeability, excellent chemical inertness and high and low temperature resistance. However, there are two technical bottlenecks in the composite of fluororesin and carbon fiber: 1. Poor interfacial bonding: the surface energy of fluororesin is extremely low, which is a difficult-to-bond material, and the wettability and adhesion strength of carbon fiber are extremely poor, so direct compounding will cause serious decrease of mechanical properties. 2. Difficult to process: the melting point of fluororesin is high, and the melt viscosity is large, so it is difficult to achieve good wetting of carbon fiber bundle, resulting in weak interfacial bonding ability and easy to produce pores.

[0006] In view of the above problems, how to effectively solve the liquid oxygen compatibility and leakage of carbon fiber composite materials in low temperature medium is a technical problem to be solved urgently. SUMMARY

[0007] One of the purposes of the present application is to provide a preparation method of low-temperature-resistant and anti-leakage carbon fiber reinforced composite material. The present application adopts a multi-level interface structure with liquid oxygen compatibility and high toughness, combined with a high anti-leakage thermoplastic resin, to prepare an effective anti-low-temperature-medium-leakage carbon fiber reinforced fluororesin composite material.

[0008] In order to achieve the above purpose, the technical scheme adopted by the present application is as follows: A preparation method of low-temperature-resistant and anti-leakage carbon fiber reinforced composite material, comprising the following steps: (1) dispersing polyamide acid grafted hydroxylated nano silicon dioxide in a solvent to obtain a polyamide acid grafted hydroxylated nano silicon dioxide solution, and then adding nano rubber and ultrasonic treatment to obtain a sizing agent; (2) The carbon fiber is subjected to desizing treatment to obtain desized carbon fiber, which is immersed in the sizing agent obtained in step (1), taken out and dried to obtain sized carbon fiber; (3) The polytrifluorochloroethylene resin is uniformly spread on the sized carbon fiber obtained in step (2), hot-pressed and immersed, cooled and shaped, and wound to obtain carbon fiber reinforced polytrifluorochloroethylene prepreg tape; (4) The polytrifluorochloroethylene resin is uniformly spread on the sized carbon fiber obtained in step (2), hot-pressed and immersed, cooled and shaped, and wound to obtain carbon fiber reinforced polytrifluorochloroethylene prepreg tape; (5) The carbon fiber reinforced polytrifluorochloroethylene prepreg tape is laid in the inner layer, and the carbon fiber reinforced polytrifluorochloroethylene prepreg tape is laid in the outer layer, and cured and formed.

[0009] Further, in step (1), the polyamic acid grafted hydroxylated nanosilica comprises the following steps: The condensing agent and the catalyst are added to the polyamic acid diluent solution to obtain a mixed solution; under a nitrogen atmosphere, the mixed solution is added to the hydroxylated nanosilica dispersion, heated and stirred, and the reacted mixture is centrifuged, washed, dried, and the polyamic acid grafted hydroxylated nanosilica is obtained.

[0010] The composite material of the present application comprises an anti-permeation layer and a load-bearing layer arranged in sequence from inside to outside; the anti-permeation layer is formed by laying the carbon fiber reinforced polytrifluorochloroethylene prepreg tape formed by impregnating sized carbon fiber with polytrifluorochloroethylene; and the load-bearing layer is formed by laying the carbon fiber reinforced polytrifluorochloroethylene prepreg tape formed by impregnating sized carbon fiber with polytrifluorochloroethylene.

[0011] The sized carbon fiber of the present application has a multi-level reinforced interface layer on the surface, which is composed of polyamic acid (PAA) grafted hydroxylated nanosilica (OH-SiO2) and nanorubber.

[0012] a. The polar groups (carboxyl, amide groups) in the polyamic acid (PAA) molecular chain can form strong van der Waals forces and hydrogen bonds with the active groups on the surface of the carbon fiber. In addition, during the hot-pressing and curing and forming process, PAA will be converted into polyimide (PI), and the PAA molecular chain can interdiffuse and entangle with the resin chains of polytrifluorochloroethylene resin (PCTFE), PES (polyether sulfone resin) / PPS (polyphenylene sulfide resin), etc., forming a gradient interpenetrating structure, which improves the bonding ability of carbon fiber and PCTFE, PES / PPS, and forms a carbon fiber composite material with a laminated structure. That is, the introduction of polyamic acid grafted hydroxylated nanosilica not only improves the interface bonding between the resin matrix and the carbon fiber, but also improves the density of the composite material, and improves its impermeability and compatibility after high-low temperature cycling.

[0013] b.Ordinary silica is easy to agglomerate in the resin matrix, resulting in a decrease in the mechanical properties of the material and destroying the density of the material, while the carboxyl groups on the PAA chain and the hydroxyl groups on the surface of the hydroxylated nano-silica are reacted to graft the hydroxylated nano-silica to the PAA, which stably exists in the sizing agent and is ultimately uniformly distributed on the surface of the carbon fiber, improving the strength and interface density of the material.

[0014] c.In the present application, the nano-rubber particles can be uniformly dispersed in the polyamic acid (PAA) grafted hydroxylated nano-silica solution, thereby effectively preventing agglomeration. During the subsequent heat pressing and curing process, the PAA molecular chain will shrink and entangle, and the nano-rubber particles will be fixed in the formed polyimide (PI) network. This ensures that the nano-rubber particles are firmly fixed in the interface region of the fiber and the resin, and will not migrate or be lost during processing.

[0015] Further, the molar ratio of the polyamic acid, the condensing agent and the catalyst is 1: (1.2-1.5): (0.1-0.2), the mass ratio of the mixed solution and the hydroxylated nano-silica dispersion is (1-3):2; the concentration of the hydroxylated nano-silica dispersion is 8-12wt%; the condensing agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, the catalyst is 4-N,N-dimethylpyridine, the solvent in the hydroxylated nano-silica dispersion is N,N-dimethylformamide, and the concentration of the polyamic acid dilution is 1-5wt%; the polyamic acid dilution is obtained by diluting the polyamic acid stock solution with DMF.

[0016] Further, the temperature of the heating and stirring is 70-80℃, and the time is 20-24h.

[0017] Further, in step (1), the mass ratio of the nano-rubber and the polyamic acid grafted hydroxylated nano-silica solution is (0.5-3):(97-99.5); the concentration of the polyamic acid grafted hydroxylated nano-silica solution is 1-3wt%; the solvent is N,N-dimethylformamide; and the nano-rubber is a core-shell structure with a polybutadiene rubber core and a polymethyl methacrylate shell, and the particle size is 50nm.

[0018] Further, in step (1), the ultrasonic treatment comprises: using 800-1000W power ultrasonic for 5-10min, and then using 300-500W power ultrasonic for 20-30min; the slurry temperature is controlled to be ≤40℃ during the ultrasonic treatment, and the absolute value of Zeta potential of the slurry after dispersion is greater than 35mV; in step (2), the temperature of the desmearing treatment is 350-450℃, and the time is 0.5-5min; the time of the impregnation is 25-30s; and the temperature of the drying is 140-180℃.

[0019] Further, in step (3), the temperature of the hot-pressing impregnation is 250-260℃, and the pressure is 0.5-2 MPa; the temperature of the cooling and shaping is 10-20℃; in step (4), the temperature of the hot-pressing impregnation is 310-320℃, and the pressure is 1-3 MPa; and the temperature of the cooling and shaping is 10-20℃.

[0020] Further, in step (5), the conditions of the solidification and forming are as follows: increasing the temperature from room temperature to 300-310℃ at a rate of 8-10℃ / min, and then keeping at 0.5-1MPa, 4-5MPa and 2-3MPa respectively for 5-10min, and then decreasing to room temperature.

[0021] Further, in step (5), the thickness of the carbon fiber reinforced polytrifluorochloroethylene prepreg tape is 0.2-0.5mm, and the thickness of the carbon fiber reinforced polyether sulfone / polyphenylene sulfide resin prepreg tape is 1.0-1.5mm.

[0022] The second object of the present application is to provide a low-temperature-resistant anti-permeation carbon fiber reinforced composite material.

[0023] The low-temperature-resistant anti-permeation carbon fiber reinforced composite material is prepared by the above preparation method.

[0024] Compared with the prior art, the present application has the following beneficial effects: 1、The present application provides a low-temperature-resistant anti-permeation carbon fiber reinforced composite material, which can maintain high mechanical properties and has ultra-low permeability and compatibility under ultra-low temperature cycles. -8 Pa·m 3 / s under 3MPa in a liquid nitrogen environment; (2) the interlaminar shear strength (ILSS) retention rate is ≥90%; and (3) the material has good liquid oxygen compatibility.

[0025] 2. The application provides a preparation method of a low-temperature-resistant anti-carburization carbon fiber reinforced composite material, which is simple and easy to implement, suitable for industrialization and mass application, and the development of the carbon fiber composite material can be used for preparing aerospace propellant storage tanks, high and low temperature tanks and the like, thereby providing strong support for technical innovation and industrial upgrading in related fields. DETAILED DESCRIPTION

[0026] The technical solutions of the application are further explained and described below in combination with specific examples, comparative examples and test examples.

[0027] In the following examples, comparative examples and test examples, the raw materials and preparation methods used are conventional materials and technologies in the field unless otherwise specified.

[0028] The hydroxylated nanosilica in the application is purchased from Nanjing Xianfeng Nanometer Material Technology Co., Ltd., and the model number is XFnano-SiO2-20H: 20 nm.

[0029] The polyamide acid (PAA) stock solution in the application is purchased from Shandong Liaocheng Tongda Chemical Co., Ltd., and is a N,N-dimethylformamide (DMF) system PAA solution with a solid content of 15wt%.

[0030] The nanorubber particles in the application are purchased from Shanghai Napai New Material Co., Ltd., and the nanorubber particles have a core-shell structure, the inner core is polybutadiene rubber, and the outer shell is polymethyl methacrylate, and the particle size is 50 nm.

[0031] The polychlorotrifluoroethylene resin (PCTFE) in the application is purchased from Zhengyu New Material Technology Co., Ltd.

[0032] The polyether sulfone resin (PES) in the application is purchased from BASF SE.

[0033] The polyphenylene sulfide resin (PPS) in the application is purchased from Suzhou Nalan New Material Technology Co., Ltd.

[0034] The carbon fiber in the application is purchased from Jiangsu Hengshen Co., Ltd., and the model number is T1100.

[0035] Preparation Example The preparation method of the polyamide acid grafted hydroxylated nanosilica comprises the following steps: S1. Hydroxylated nanosilica (OH-SiO2) powder is added to a three-necked flask containing N,N-dimethylformamide (DMF), and ultrasonic dispersion is performed in an ice water bath for 60 min at a power of 600W using a probe type ultrasonic instrument to obtain a semi-transparent or milky white OH-SiO2 dispersion liquid (concentration of 10wt%); nitrogen is continuously introduced into the system to exclude air and moisture.

[0036] S2. Take polyamide acid (PAA) stock solution, dilute with DMF to obtain 5 wt% PAA dilution; in another container, add condensing agent 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and catalyst 4-N,N-dimethylpyridine (DMAP) to the PAA dilution, wherein the molar ratio of PAA, EDC and DMAP is 1:1.5:0.1, stir at room temperature for 30 min to obtain a mixed solution.

[0037] S3. Slowly drop the mixed solution in step S2 into the OH-SiO2 dispersion using a constant pressure dropping funnel, the mass ratio of the mixed solution and the OH-SiO2 dispersion is 1:1, stir at 70°C under nitrogen protection and continuous stirring, the stirring rate is 500 rpm, react for 20 h.

[0038] S4. Transfer the reaction product mixture to a centrifuge tube, centrifuge using a high-speed centrifuge, the centrifugal speed is 10000 rpm, centrifuge for 3 times, each time for 5 min, wash the precipitate with acetone and ethanol alternately for 3 times; place the finally obtained product in a vacuum drying oven, dry at 80°C for 24 h to obtain polyamide acid grafted hydroxylated nano silica.

[0039] Example 1 A preparation method of a low-temperature-resistant anti-carburization carbon fiber reinforced composite material, comprising the following steps: (1) Disperse polyamide acid grafted hydroxylated nano silica in DMF to obtain a 2 wt% polyamide acid grafted hydroxylated nano silica solution, then add nano rubber (the mass ratio of nano rubber and polyamide acid grafted hydroxylated nano silica solution is 2:98); perform stepwise ultrasonic dispersion treatment: first use 900 W power ultrasonic for 8 min, then use 400 W power ultrasonic for 25 min; control the slurry temperature ≤40°C during ultrasonic dispersion, the absolute value of the Zeta potential of the slurry after dispersion is greater than 35 mV, to obtain a sizing agent; (2) Treat carbon fiber at 400°C for 1 min to obtain desized carbon fiber, immerse the desized carbon fiber in the sizing agent obtained in step (1), take out after 20 s of immersion, and volatilize the solvent at 150°C; to obtain sized carbon fiber; (3) Vacuum dry polytrifluorochloroethylene resin (PCTFE) at 100°C for 6 h, then evenly spread PCTFE on the sized carbon fiber developed in step (2), immediately pass through a high-temperature hot roller, the temperature is set to 250°C, roll and immerse the sized carbon fiber in the molten resin under a pressure of 2 MPa, then immediately pass through a cooling roller, the temperature is 20°C, to quench and shape the resin; wind up to obtain a carbon fiber reinforced polytrifluorochloroethylene prepreg tape; (4) The polyether sulfone resin (PES) and polyphenylene sulfide resin (PPS) blended pellets are dried at 100°C for 6h. The dried blended resin is melt plasticized through an extruder at a temperature of 310°C, and the melt is directly coated on the sized carbon fibers developed in step (2) through a slit die, and immediately passed through a high-temperature hot roller with a temperature setting of 310°C to complete the impregnation under a pressure of 2MPa; then immediately passed through a cooling roller with a temperature of 10°C to quench and shape the resin; and wound up to obtain a carbon fiber reinforced polyether sulfone / polyphenylene sulfide resin prepreg tape; (5) The carbon fiber reinforced polytrifluorochloroethylene prepreg tape is laid in the inner layer (thickness 0.2mm) as a barrier layer; and the carbon fiber reinforced polyether sulfone / polyphenylene sulfide resin prepreg tape is laid in the outer layer (thickness 1.4mm) as a load-bearing layer; and a hot-pressing forming process is used: rapidly increasing the temperature from room temperature to 300°C at a rate of 10°C / min, and after reaching 300°C, maintaining at 0.5MPa, 5MPa and 2MPa for 5min respectively, and then decreasing to room temperature; and the product is obtained.

[0040] The embodiment also provides a low-temperature-resistant and barrier-resistant carbon fiber reinforced composite material prepared by the above preparation method.

[0041] Example 2 A preparation method of a low-temperature-resistant and barrier-resistant carbon fiber reinforced composite material, comprising the following steps: (1) Polyamide acid grafted hydroxylated nano-silica is dispersed in DMF to obtain a 1wt% polyamide acid grafted hydroxylated nano-silica solution, and then nano-rubber is added (the mass ratio of nano-rubber to the polyamide acid grafted hydroxylated nano-silica solution is 0.5:99.5); the slurry is subjected to stepwise ultrasonic dispersion treatment: first ultrasonic dispersion is performed at a power of 800W for 10min, and then ultrasonic dispersion is performed at a power of 300W for 30min; the slurry temperature is controlled to be ≤40°C during the ultrasonic dispersion process, and the absolute value of the Zeta potential of the slurry after dispersion is greater than 35mV to obtain a sizing agent; (2) Carbon fibers are desized at 350°C for 5min to obtain desized carbon fibers, the desized carbon fibers are immersed in the sizing agent obtained in step (1), taken out after 20s of immersion, and the solvent is volatilized at 140°C; and sized carbon fibers are obtained; (3) PCTFE is vacuum dried at 100°C for 6h, and then the PCTFE is uniformly spread on the sized carbon fibers developed in step (2), and immediately passed through a high-temperature hot roller with a temperature setting of 255°C to roll and impregnate the sized carbon fibers with the molten resin under a pressure of 0.5MPa, and then immediately passed through a cooling roller with a temperature of 10°C to quench and shape the resin; and wound up to obtain a carbon fiber reinforced polytrifluorochloroethylene prepreg tape; (4) The PES and PPS blended granules are dried at 100°C for 6h. The dried blended resin is melt plasticized through an extruder at a temperature of 315°C, and the melt is directly coated on the sized carbon fibers developed in step (2) through a slit die, and immediately passed through a high-temperature hot roller with a temperature setting of 315°C to complete impregnation at 3MPa, and then immediately passed through a cooling roller with a temperature of 20°C to quench and set the resin. The carbon fiber reinforced polyether sulfone / polyphenylene sulfide resin prepreg tape is obtained by winding. (5) The carbon fiber reinforced polytrifluorochloroethylene prepreg tape is laid in the inner layer (thickness 0.5mm) as a barrier layer, and the carbon fiber reinforced polyether sulfone / polyphenylene sulfide resin prepreg tape is laid in the outer layer (thickness 1.0mm) as a load-bearing layer. A hot-pressing forming process is used: rapid heating to 305°C, and after reaching 305°C, maintaining at 0.5MPa, 5MPa, and 2MPa for 8min respectively, and then reducing to room temperature. The low-temperature-resistant and barrier-resistant carbon fiber reinforced composite material is obtained.

[0042] The embodiment also provides a low-temperature-resistant and barrier-resistant carbon fiber reinforced composite material prepared by the above preparation method.

[0043] Example 3 A preparation method of a low-temperature-resistant and barrier-resistant carbon fiber reinforced composite material, comprising the following steps: (1) Polyamide acid grafted hydroxylated nano-silica is dispersed in DMF to obtain a 2wt% polyamide acid grafted hydroxylated nano-silica solution, and then nano-rubber is added (the mass ratio of nano-rubber to the polyamide acid grafted hydroxylated nano-silica solution is 3:97); the slurry is subjected to stepwise ultrasonic dispersion treatment: first ultrasonic dispersion at a power of 1000W for 5min, and then ultrasonic dispersion at a power of 500W for 20min; the slurry temperature is controlled to be ≤40°C during ultrasonic dispersion, and the absolute value of the Zeta potential of the dispersed slurry is greater than 35mV, to obtain a sizing agent; (2) Carbon fibers are desized at 450°C for 0.5min to obtain desized carbon fibers, which are immersed in the sizing agent obtained in step (1) for 25s, and then taken out and the solvent is volatilized at 180°C to obtain sized carbon fibers; (3) PCTFE is vacuum dried at 100°C for 6h, and then uniformly spread on the sized carbon fibers developed in step (2), and immediately passed through a high-temperature hot roller with a temperature setting of 260°C to roll and impregnate the sized carbon fibers with the melt resin at a pressure of 1MPa, and then immediately passed through a cooling roller with a temperature of 15°C to quench and set the resin. The carbon fiber reinforced polytrifluorochloroethylene prepreg tape is obtained by winding. (4) The PES and PPS blended granules are dried at 100°C for 6h. The dried blended resin is melt plasticized through an extruder at a temperature of 320°C, and the melt is directly coated on the sized carbon fibers developed in step (2) through a slit die, and immediately passed through a high-temperature hot roller with a temperature setting of 320°C to complete impregnation under 1 MPa; then immediately passed through a cooling roller with a temperature of 15°C to quench and shape the resin; and wound up to obtain a carbon fiber reinforced polyether sulfone / polyphenylene sulfide resin prepreg tape; (5) The carbon fiber reinforced polychlorotrifluoroethylene prepreg tape is laid in the inner layer (thickness 0.2mm) as a barrier layer; the carbon fiber reinforced polyether sulfone / polyphenylene sulfide resin prepreg tape is laid in the outer layer (thickness 1.5mm) as a load-bearing layer; and hot-pressing and curing molding is performed: rapid heating to 310°C, and after reaching 310°C, maintaining at 0.5 MPa, 5 MPa and 2 MPa for 5 min respectively, and then reducing to room temperature; and thus obtained.

[0044] The embodiment also provides a low-temperature-resistant and barrier carbon fiber reinforced composite material prepared by the above preparation method.

[0045] Comparative Example 1 Comparative Example 1 and Example 1 differ in that the dispersing of the polyamide acid grafted hydroxylated nano-silica in DMF in step (1) is replaced by dispersing the polyamide acid and nano-silica in DMF.

[0046] Comparative Example 2 Comparative Example 2 and Example 1 differ in that the dispersing of the polyamide acid grafted hydroxylated nano-silica in DMF in step (1) is replaced by dispersing the polyamide and hydroxylated nano-silica in DMF.

[0047] Comparative Example 3 Comparative Example 3 and Example 1 differ in that the PCTFE in step (3) is replaced by an epoxy resin.

[0048] Comparative Example 4 Comparative Example 4 and Example 1 differ in that step (4) is omitted, and the load-bearing layer in step (5) is replaced by a carbon fiber reinforced polychlorotrifluoroethylene prepreg tape.

[0049] Test Example 1 The properties of the composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were tested: the leak rate was tested by helium mass spectrometry leak detection under the following conditions: liquid nitrogen environment, 3 MPa pressure; the interlaminar shear strength (ILSS) was characterized by ASTM 2344; the materials were cycled 50 times between -196°C and 120°C, and then the leak rate, interlaminar shear strength of the materials were tested again, and the liquid oxygen compatibility of the materials was tested. The ILSS retention rate = (ILSS after 50 cycles / ILSS before cycling) x 100%; the results are shown in Table 1.

[0050] Table 1 As can be seen from the experimental results in Table 1, the carbon fiber composite material of the present application has an ultra-low leak rate and interlaminar shear strength. After 50 high-low temperature cycles between -196°C and 120°C, the leak rate of the carbon fiber composite material still maintains , the interlaminar shear strength (ILSS) retention rate is ≥90%; it has good liquid oxygen compatibility. Among them, the comprehensive performance of Examples 1-3 is generally better than that of Comparative Examples 1-4.

[0051] Compared with Example 1, the leak rate, interlaminar shear strength, and high-low temperature cycle resistance of Comparative Example 1 are all poor. The reason for this is that a series of chain reactions caused by the lack of hydroxyl groups on the surface of the nanosilica: its dispersibility and grafting reactivity with polyamic acid are poor, which directly weakens the interfacial bonding strength after sizing of the carbon fiber. An insufficiently bonded interface cannot fully absorb external load energy, nor can it effectively inhibit the initiation and propagation of microcracks, which makes the composite material more prone to interface failure and medium leakage when stressed. Therefore, its initial ILSS value is low and the leak rate is high. After cyclic loading or environmental aging, this inherent interface defect becomes a stress concentration point, leading to accelerated accumulation of damage, so the ILSS retention rate after cycling is significantly reduced, and the leakage phenomenon is further aggravated.

[0052] Compared with Example 1, the helium leak rate of Comparative Example 2 is significantly reduced, and the interlaminar shear strength before and after cycling is also significantly reduced compared with Example 1. The reason for the decrease is as follows: the hydrogen bond between the polyimide and the hydroxylated nanosilica is mainly in the form of hydrogen bond, and no covalent bond is formed. Compared with a firm chemical bond, hydrogen bond as a weaker physical interaction has lower binding energy and is prone to dissociation under stress, which limits its effectiveness in strengthening the interface between carbon fiber and resin. This interface becomes a weak link under thermal cyclic loading (such as heat and force), and cannot effectively inhibit the initiation and propagation of microcracks, so the interfacial shear strength and leak rate will decrease before and after cycling, and the retention rate is low and the leak rate increases significantly.

[0053] Compared with Example 1, the helium leakage rate before cycling and the interlaminar shear strength of Comparative Example 3 are significantly reduced, the helium leakage rate after cycling and the interlaminar shear strength are the worst, and it does not have liquid oxygen compatibility, and the reasons for the decrease are as follows: since the use temperature of the epoxy resin is far lower than 300 DEG C, and it is a thermosetting plastic, it does not have the ability of secondary molding, when it is co-molded with the carbon fiber reinforced polyether sulfone / polyphenylene sulfide (PES / PPS) thermoplastic prepreg tape, the two cannot form a good interface fusion. Therefore, obvious interface separation occurs in the obtained composite material, including the carbon fiber / epoxy resin part and the carbon fiber / PES / PPS part. The bonding force of the two-phase interface of the structure is insufficient, resulting in a significant decrease in the interlaminar shear strength (ILSS); the epoxy resin itself does not have liquid oxygen compatibility, further limiting its applicability in a liquid oxygen environment; the carbon fiber / epoxy resin as a barrier layer is prone to interface debonding under high and low temperature alternating stress, and cannot effectively block the penetration of the medium, thereby causing serious leakage after cycling.

[0054] Compared with Example 1, Comparative Example 4 has a significantly higher bulk mechanical property of polyphenylene sulfide (PPS) resin than that of polychlorotrifluoroethylene (PCTFE), so that the interlaminar shear strength (ILSS) of the product obtained by Comparative Example 4 is always lower than that of Example 1, and the difference still exists after the cycling test. In terms of barrier performance, PCTFE itself is an excellent barrier material, so the final barrier performance of the two is similar.

[0055] The carbon fiber composite material prepared by the present application not only has an ultra-low leakage rate under ultra-low temperature cycling, but also has high super mechanical properties and compatibility. In summary, the sizing carbon fiber in the present application has good interface bonding capacity in the mixed resin of polychlorotrifluoroethylene resin and polyether sulfone resin and polyphenylene sulfide resin, and forms a carbon fiber composite material with a multi-layer structure during the curing process. The polyamide acid forms polyimide during the curing process, can uniformly fix silica and nano rubber on the surface of the carbon fiber, and more importantly, can further improve the strength of the composite material and its barrier property under high and low temperature cycling, interlaminar shear strength, etc.

[0056] The above is only a preferred embodiment of the present application, which is not limited to the above examples. Those skilled in the art can make various modifications and changes under the principle of the present application. Any modification, improvement, etc. shall be considered within the scope of protection of the present application.

[0057] Finally, it should be pointed out that the above examples are only used to illustrate the technical solutions of the present application and are not limited to the above examples. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced equivalently without departing from the purpose and scope of the present application, and they should be covered in the scope of the claims of the present application.

Claims

1. A method for preparing a low-temperature resistant, impermeable carbon fiber reinforced composite material, characterized in that, Includes the following steps: (1) Disperse polyamic acid-grafted hydroxylated nano silica in a solvent to obtain a polyamic acid-grafted hydroxylated nano silica solution, and then add nano rubber for ultrasonic treatment to obtain a sizing agent; (2) The carbon fiber is desized to obtain desized carbon fiber, which is then immersed in the sizing agent obtained in step (1), removed and dried to obtain sized carbon fiber. (3) Spread polychlorotrifluoroethylene resin evenly onto the sized carbon fiber obtained in step (2), hot press impregnate, cool and shape, and wind up to obtain carbon fiber reinforced polychlorotrifluoroethylene prepreg tape. (4) After blending polyethersulfone resin and polyphenylene sulfide resin, melt plasticize them, coat them onto the sized carbon fiber obtained in step (2), hot press impregnate, cool and shape, and wind up to obtain carbon fiber reinforced polyethersulfone / polyphenylene sulfide resin prepreg tape. (5) Lay carbon fiber reinforced polychlorotrifluoroethylene prepreg tape in the inner layer and carbon fiber reinforced polyethersulfone / polyphenylene sulfide resin prepreg tape in the outer layer, and cure to form the desired shape.

2. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 1, characterized in that, In step (1), the polyamic acid-grafted hydroxylated nano-silica includes the following steps: A condensing agent and a catalyst are added to a polyamic acid diluent to obtain a mixed solution. Under a nitrogen atmosphere, the mixed solution is added to a hydroxylated nano-silica dispersion, heated and stirred. The reacted mixture is then centrifuged, washed, and dried to obtain polyamic acid-grafted hydroxylated nano-silica.

3. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 2, characterized in that, The molar ratio of the polyamic acid, condensing agent, and catalyst is 1:(1.2-1.5):(0.1-0.2), and the mass ratio of the mixed solution to the hydroxylated nano-silica dispersion is (1-3):2; the concentration of the hydroxylated nano-silica dispersion is 8-12 wt%; the condensing agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, the catalyst is 4-N,N-dimethylpyridine, the solvent in the hydroxylated nano-silica dispersion is N,N-dimethylformamide, and the concentration of the polyamic acid diluent is 1-5 wt%; the polyamic acid diluent is obtained by diluting the polyamic acid stock solution with DMF.

4. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 2, characterized in that, The heating and stirring temperature is 70-80℃, and the time is 20-24h.

5. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 1, characterized in that, In step (1), the mass ratio of the nano-rubber to the polyamic acid-grafted hydroxylated nano-silica solution is (0.5-3):(97-99.5); the concentration of the polyamic acid-grafted hydroxylated nano-silica solution is 1-3 wt%; the solvent is N,N-dimethylformamide; the nano-rubber has a core-shell structure, with a core of polybutadiene rubber and a shell of polymethyl methacrylate, and a particle size of 50 nm.

6. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 1, characterized in that, In step (1), the ultrasonic treatment includes: ultrasonication with 800-1000W power for 5-10 minutes, followed by ultrasonication with 300-500W power for 20-30 minutes; the slurry temperature is controlled to be ≤40℃ during the ultrasonic treatment; in step (2), the deslurry treatment temperature is 350-450℃ and the time is 0.5-5 minutes; the impregnation time is 25-30 seconds; and the drying temperature is 140-180℃.

7. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 1, characterized in that, In step (3), the temperature of hot pressing and impregnation is 250-260℃ and the pressure is 0.5-2MPa; the temperature of cooling and shaping is 10-20℃; in step (4), the temperature of hot pressing and impregnation is 310-320℃ and the pressure is 1-3MPa; the temperature of cooling and shaping is 10-20℃.

8. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 1, characterized in that, In step (5), the curing conditions are as follows: the temperature is increased from room temperature to 300-310℃ at a rate of 8-10℃ / min, and then maintained at 0.5-1MPa, 4-5MPa and 2-3MPa for 5-10min respectively, and then reduced to room temperature.

9. The method for preparing the low-temperature resistant and impermeable carbon fiber reinforced composite material according to claim 1, characterized in that, In step (5), the thickness of the carbon fiber reinforced polychlorotrifluoroethylene prepreg tape is 0.2-0.5 mm, and the thickness of the carbon fiber reinforced polyethersulfone / polyphenylene sulfide resin prepreg tape is 1.0-1.5 mm.

10. A low-temperature resistant and impermeable carbon fiber reinforced composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of carbon fiber enhanced polyimide based composite material

    CN109265998A

  • Carbon fiber sizing agent, preparation method of carbon fiber sizing agent, sized carbon fiber and preparation method of sized carbon fiber

    CN119615625A

  • Carbon fiber reinforced composite material for aerospace low-temperature storage tank and preparation method of carbon fiber reinforced composite material

    CN121181948A

  • Sizing agent, carbon fiber, prepreg, carbon fiber-reinforced composite material and method for producing carbon fiber

    JP2023111335A